Developing disabled entrepreneurial graduates: A mission for the Nigerian universities? - Dakung, Reuel Johnmark; Munene, John; Balunywa, Waswa; Ntayi, Joseph; Ngoma, Mohammed (Journal of Research in Innovative Teaching & Learning, 2019)
The purpose of this paper is to investigate the role of universities in preparing disabled students to become entrepreneurially inclined after graduation with the aim of developing an entrepreneurial inclination (EI) model. Design/methodology/approach – A cross-sectional survey was employed using 220 disabled universities’ students in the north-central Nigeria. Data were analyzed using descriptive statistics, correlation analysis and structural equation model. All analyses were performed using SPSS version 22 and AMOS version 22. Findings – The findings buttress the significant position of universities in promotion entrepreneurial spirit. It revealed that the university’s role (UR), entrepreneurship education (EE) and role models (RMs) have a positive influence on disabled students’ EI. Universities that make provisions for entrepreneurship infrastructure, knowledge and RMs to disabled students will boost their EI. Second, the more lecturers and RMs inspire students, method of teaching and demonstrating enthusiasm are applied in the teaching of entrepreneurship, the better it prepares students for entrepreneurial career after graduation. Research limitations/implications – The study is only restricted to Federal Universities in the North-Central Nigeria. Further research could be conducted to cover other tertiary institutions in North-Central Nigeria. Furthermore, the study employed the cross-sectional approach. A longitudinal approach should be employed to study the trend over a period of at least two years. Finally, the factors identified in triggering EI may not be sufficient enough in explaining the phenomenon. There are other factors that may contribute in influencing EI of the disabled students that were not part of this study. Practical implications – This study indicates a number of implications for the universities and policy makers. Specifically, EE, UR and RMs make significant contributions to inclination for disabled students. These factors are key for universities in Nigeria to consider in preparing these students to become entrepreneurial graduates. Policy makers and other stakeholders need to develop keen interest in designing entrepreneurship curriculum to accommodate the specific needs of students with disabilities. Originality/value – This study is the first in Nigeria to empirically test the relationship between UR, EE and EI as well as the moderating effect of RMs among universities’ disabled students.
Keywords: Entrepreneurship education; Role models; Entrepreneurial inclination; University’s role